A Study on Medicinal Plants and Traditional Medicine: Exploring the historical use of herbs in medicinal practices (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Long before the prehistoric era, people used plants for medicinal purposes. Chinese writings,Egyptian papyrus, and ancient Unani manuscripts all discussed the use of herbs. There is evidence thatover 4000 years ago, Unani Hakims, Indian Vaids, and cultures from the Mediterranean and Europe usedherbs as medicine. Herbs were used in healing rituals by indigenous cultures in Rome, Egypt, Iran,Africa, and America, while other cultures developed traditional medical systems like Unani, Ayurveda,and Chinese Medicine that systematically used herbal therapies.